2020
DOI: 10.1186/s13046-020-01621-y
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial ROS accumulation inhibiting JAK2/STAT3 pathway is a critical modulator of CYT997-induced autophagy and apoptosis in gastric cancer

Abstract: Background: Gastric cancer (GC) is a common form of malignant cancer in worldwide which has a poor prognosis. Despite recent improvements in the treatment of GC, the prognosis is not yet satisfactory for GC patients. CYT997, a novel microtubule-targeting agent, recently has been identified to be a promising anticancer candidate for the treatment of cancers; however, the effects of CYT997 in GC remain largely unknown. Methods: Cell proliferation and apoptosis were detected by CCK8 assay and flow cytometry. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 48 publications
6
48
0
Order By: Relevance
“… 33 In addition, several papers proved that the anti-cancer strategy that triggers ROS generation in cancer cells to induce apoptosis is indeed feasible. 31 , 34–36 According to the present study, apoptosis and the production of ROS in tumor tissues were promoted by SZYY ( Figure 2A and B ), which suggests the increased level of oxidative stress in tumor tissue and the resulting apoptosis/death of tumor cells may also be one of the main mechanisms underlying the anti-melanoma effects of SZYY.…”
Section: Discussionsupporting
confidence: 64%
“… 33 In addition, several papers proved that the anti-cancer strategy that triggers ROS generation in cancer cells to induce apoptosis is indeed feasible. 31 , 34–36 According to the present study, apoptosis and the production of ROS in tumor tissues were promoted by SZYY ( Figure 2A and B ), which suggests the increased level of oxidative stress in tumor tissue and the resulting apoptosis/death of tumor cells may also be one of the main mechanisms underlying the anti-melanoma effects of SZYY.…”
Section: Discussionsupporting
confidence: 64%
“…On the contrary, ERK, which is activated by growth factors, is considered pro-survival and oncogenic, and it antagonizes apoptosis by phosphorylating proapoptotic Bax and antiapoptotic Bcl-2 proteins, inhibiting and promoting their functions, respectively ( Figure 2 ) [ 87 ]. Activated ROS production also plays a role in JAK2/STAT3 signaling suppression and subsequent apoptosis induction; for example, Cao et al demonstrated that CYT997, a novel synthetic microtubule-disrupting agent, through the upregulation of mitochondrial ROS, triggers protective autophagy and inhibits the JAK2/STAT3 pathway, inducing gap 2 (G2)/mitosis (M) arrest and apoptosis in gastric cancer cells [ 88 ].…”
Section: Mitochondrial Ros Involvement In Cancermentioning
confidence: 99%
“…Meanwhile, we inhibited the activation of JAK2 with the JAK2 inhibitor AG490 and found that AG490 significantly decreased the levels of phosphorylated JAK2 and STAT3 in U251 cells treated with the combination of sorafenib and TMZ ( Figure 7B and Supplementary Figure 7B ). Previous reports have revealed that ROS are involved in the JAK2/STAT3 pathway ( Cao et al, 2020 ); thus, we examined the effect of ROS on the JAK2/STAT3 pathway. As shown in Figure 7D , intracellular ROS were overproduced in U251 cells treated with the combination of sorafenib and TMZ compared with cells treated with either single agent alone.…”
Section: Resultsmentioning
confidence: 99%